Improving Students’ Scientific Literacy Skills Using Inquiry- Based E-Comic At The Tenth Grader In Lampung Province - Priadi, Median Agus; Trisna Dewi, Sayu Kadek; Wisnu Prabowo, Galuh Catur (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
This study aims to determine the effect of inquiry-based e-comic media on students' scientific literacy abilities and to determine students' responses to inquiry-based e-comic. This type of research is a quasi experiment; The sample in the study was taken using the cluster random sampling technique; The research data was taken through the pretest and posttest to see the increase in scientific literacy skills after the learning process while the use of a questionnaire in the experimental class was used to find out students' responses to e-comic media; The results showed that there was a significant effect of the use of inquiry-based e-comic media on students' scientific literacy skills with a significance value of the independent sample t-test of 0.000 or less than 0.05; The results of the questionnaire on student responses to inquiry-based e-comic media obtained an average percentage of 86% in the very good category ABSTRAK: Penelitian ini bertujuan untuk mengetahui pengaruh media ecomic berbasis inquiry terhadap kemampuan literasi sains peserta didik serta mengetahui tanggapan peserta didik terhadap e-comic berbasis inquiry. Jenis penelitian ini adalah quasi eksperimen; Sampel dalam penelitian diambil menggunakan teknik Cluster random sampling; Data penelitian diambil melalui pretest dan posttest untuk melihat peningkatan kemampuan literasi sains setelah proses pembelajaran sedangkan penggunaan angket di kelas eksperimen digunakan untuk mengetahui tanggapan peserta didik terhadap media e-comic; Hasil penelitian menunjukkan terdapat pengaruh yang signifikan penggunaan media ecomic berbasis inquiry terhadap kemampuan literasi sains peserta didik dengan nilai signifikansi uji independent sample t-test 0,000 atau kurang dari 0,05; Hasil angket tanggapan peserta didik terhadap media media ecomic berbasis inquiry diperoleh rata-rata persentase 86% dengan kategori sangat baik.